2021
DOI: 10.1080/21681015.2021.1950227
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable industrial and operation engineering trends and challenges Toward Industry 4.0: a data driven analysis

Abstract: This study supplies contributions to the existing literature with a state-of-the-art bibliometric review of sustainable industrial and operation engineering as the field moves towards Industry 4.0, and guidance for future studies and practical achievements. Although industrial and operation engineering is being promoted forward to sustainability, the systematization of the knowledge that forms firms' manufacturing and operations and encompasses their wide concepts and abundant complementary elements is still a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 212 publications
(123 citation statements)
references
References 76 publications
0
121
0
2
Order By: Relevance
“…Nevertheless, challenges exist in building DSCs due to the accuracy of the information, but the required data need to be collected from various sources. Therefore, to achieve sustainable development, a wellestablished SC should be extended to the application of digital technology and integrated into a firm's SC [15,17,25]. Hence, there is a need for firms to reimagine their SC process as a DSC network to reach development goals.…”
Section: Digitalization In Supply Chainmentioning
confidence: 99%
“…Nevertheless, challenges exist in building DSCs due to the accuracy of the information, but the required data need to be collected from various sources. Therefore, to achieve sustainable development, a wellestablished SC should be extended to the application of digital technology and integrated into a firm's SC [15,17,25]. Hence, there is a need for firms to reimagine their SC process as a DSC network to reach development goals.…”
Section: Digitalization In Supply Chainmentioning
confidence: 99%
“…Other recommendations have also been developed according to the considered industrial sector, such as the ones developed for the textile industry, for avoiding "overuse of resources, waste generation, environmental pollution and unethical labour condition" [76]. In the same way, the bibliometric analysis of Tseng et al [77] shows that Industry 4.0 allows the company to avoid such waste but also to ensure "a safe and secure environment that encourages more ethical and moral behaviors that can increase sustainability through mutual cooperation". However, the authors underline that even if "the socio-ethical features of CPSs .…”
Section: Ethics In Industrymentioning
confidence: 99%
“…In particular, Feil et al [2] emphasized that product quality acts as a motivator to strengthen consumers' SCI because of the benefit of health improvements. In different studies, other product features, such as availability and variety, have been found to affect consumption intention to purchase the product [7,30]. These works indicate the importance of economic considerations in consumption intentions.…”
Section: Sustainable Product Purchasing Featuresmentioning
confidence: 91%